Diversity, Abundance and Community Composition of Birds in Chitwan Annapurna Landscape, Central Nepal - Shubhas Chandra Bastola; Pradip Kandel; Hathan Ram Mahato; Jagan Nath Adhikari; Bishnu Prasad Bhattarai (Ecology and Evolution, 2025)
ABSTRACT Understanding bird diversity and composition is important for assessing survival, adaptability, and extinction risks. This study investigated bird species abundance, richness, seasonal diversity, and composition across habitats, seasons, and physiographic zones of Chitwan Annapurna Landscape (CHAL) from 2020 to 2021 using the point count method. We recorded 458 bird species with higher richness and diversity in winter (n = 365) than in summer (n = 299). This study indicates a high diversity of birds (Shannon = 5.54, Simpson = 0.99) and an even distribution of species Pielou's Evenness Index (0.90). Species richness and abundance showed seasonal and habitat‐specific variations, with wetlands highest in winter (richness: 6.94 ± 0.38, abundance: 23.10 ± 5.65) and croplands in summer (richness: 7.00 ± 0.35, abundance: 13.61 ± 1.10), while forests exhibited stability. Evenness was high across all habitats (0.90 ± 0.01 to 0.95 ± 0.00), with minimal seasonal variation. Diversity indices were highest in cropland during summer (Margalef: 2.33 ± 0.10, Shannon: 1.77 ± 0.06, Simpson: 0.80 ± 0.02) and wetlands during winter (Margalef: 2.19 ± 0.08, Shannon: 1.75 ± 0.05, Simpson: 0.79 ± 0.01); forests had moderate and stable diversity, while grasslands showed low values. We observed 2 globally vulnerable, 5 near‐threatened, 2 endangered, and 3 critically endangered species. Analysis of similarity (ANOSIM) revealed significant community differentiation (p < 0.01) across parameters, with the strongest segregation in physiographic (R = 0.09), followed by seasons (R = 0.06) and habitat types (R = 0.01). Canonical Correspondence Analysis (CCA) showed distinct habitat clusters and a strong influence of physiographic zones, with winter and wetland habitats driving species variance. This study revealed substantial differences in bird species across seasons, and each habitat offers a distinct ecological niche for bird species. This finding highlights CHAL as a hotspot for bird community. This research contributes to the conservation and management of this landscape, aiding in the protection of bird species in Nepal.